TANTANGAN PENDIDIKAN ISLAM DI WILAYAH PERBATASAN - Yayan Ridwan (Cross-border, 2021)
The many problems of life today are very difficult to overcome by the government and educators because the authorities are still directing their political interests to be turned on at the level of the world of education, so that educators are carried away by the sweetness of the dynamics of the material world. However, the spiritual values of Islam are getting thinner every day and they are only mirages. Despite this situation, the world of Islamic education is still able to offer us to be able to develop and be creative in facing and overcoming the various problems of this life. Therefore, practitioners of Islamic education must have a strong desire to make the Next Generation of the Nation more specific in the border areas of the country in order to become Islamic educators with character, innovative, professional in accordance with the guidance of the teachings of the Islamic Religion.